Therapeutic collaboration in a comfort zone: a non-improved borderline patient psychotherapy case study (Colaboración terapéutica en una zona de confort: estudio de un caso de psicoterapia de un paciente borderline que no experimentó mejoría). Issue 3 (2nd September 2022) - Ryttinger, Raquel; Serralta, Fernanda; Pires, Nuno; Basto, Isabel; Melo, Gysele; Ribeiro, Eugénia
ABSTRACT: The quality of dyad interaction seems crucial to the client's decision to drop out of psychotherapy. To characterize the client's lack of change and the patterns of therapeutic collaboration in a dropout of psychodynamic therapy for Borderline Personality Disorder (BPD), we used the Therapeutic Collaboration Coding System (TCCS) to assess collaborative work and the Assimilation of Problematic Experiences Scale (APES) to rate client change. The software GridWare was used to characterize patterns of therapeutic collaboration and the R software to describe the client's change. The dyad worked in a comfort zone for the client, with the therapist supporting the client's problematic perspective and the client responding with Safety. The APES results showed that the client did not change, remaining in control through avoidance of thinking and discussing his problematic experience. Our results challenge the potential impact of therapists' interventions on BPD clients' comfort zones, suggesting that too much focus on their Therapeutic Zone of Proximal Development's actual level might not be productive.